Software Design using Visual Basic for Application and Microsoft Excel Programming for Students - Ramadhan, Fadillah; Rukmi, Hendang Setyo; Imran, Arif; Nugraha, Cahyadi; Ferdiansyah, Risdan (Institut Teknologi Nasional, Bandung, 2020)
The rapid development of information technology has made people to have the ability to design software with a programming language. There are quite some engineers who have not mastered programming languages. It happens becausesome people think that developing software with a certain programming language is very difficult. The language is difficult to understand, the accuracy must be precise, and the user is not familiar with the platform. Difficulty in learning programming languages is a problem that is often encountered by university students, vocational students, or employees. This article describes an easy programming language training activity for beginners, namelyVisual Basic for Applications (VBA)-Ms. Excel training.The advantage of this programming language iseasy to operate because manystudentsor employees are very familiar with Ms. Excel so that the adaptation process will be easy. The results of the post-test training that was attended bystudents showed a significant increase in the ability to design programming languages.